A didactic unit for the evaluation of the use of assistive technology for access to computers in occupational therapy. Issue 46 (19th November 2021) - Pousada, Thais; Jiménez, Estíbaliz; Díez, Emiliano
Abstract : Abstract: Assistive technology (AT) is an umbrella term that refers to different devices that facilitate the performance of activity for people. Future occupational therapists (OT) must acquire specific competencies to undertake the correct selection of such devices, specifically for those that facilitate access and use the computer. To create a didactic unit to improve the competencies of OT students about assessment of AT to access computers. The didactic unit was implemented with 95 students in OT Bachelor's degree, involving teachers from 2 Spanish universities. The procedure included: definition of competencies and learning results; determination of evidence; didactic unit design, and implementation. The main result was the didactic unit, which included 4 content blocks, each one with several activities defined. The evaluation of the students was continuous, where 48.6% of them achieved a score of between 1.9 and 2.00 (the maximum). The application of the didactic unit allowed to check that students have improved their competencies and knowledge about assessment and prescription of AT for access to a computer. The selection of competencies and learning results helped in determining and embedding expertise and professional skills concerning AT for computer access.